Achievement Motivation During Covid-19 Pandemic: The Effect of Online Learning and Academic Self-Efficacy - Muhammad Abid Marzuki; Miftahussa'adah Wardi (Edukasi Islami: Jurnal Pendidikan Islam, 2021)
The COVID-19 pandemic led to changed the learning paradigm from traditional learning with face-to-face into online learning. Changes in the learning paradigm can affect the psychological condition of students. This study aims to examine the effect of online learning on academic self-efficacy and achievement motivation with a sample of 235 students of Sekolah Tinggi Agama Islam Attaqwa. Collecting data using a questionnaire and data analysis using Partial Least Square Structural Equation Modeling. The results showed that online learning had a positive and significant effect on achievement motivation and academic self-efficacy. Another finding states that academic self-efficacy has a positive effect on achievement motivation. Therefore as an implication the government through related agencies should work together to build a reliable online learning infrastructure, that is stable internet connenction, wide-reaching, and inexpensive.